SELECTION OF NUTRIENT MEDIA ENHANCING THE VIRULENT ACTIVITY OF ENTOMOPATHOGENIC FUNGI BEAUVERIA BASSIANA - Charykova, I.V.; Nekrasova, N.I.; Balpanov, D.S.; Ten, O.A. (Eurasian Journal of Applied Biotechnology, 2014)
Fungal diseases play an important role in the spread of insects, sometimes significantly reducing their number in the wild. Biopreparations based on entomopathogenic fungi Beauveria bassiana are considered to be the most promising ones, because at optimal conditions the application of the pathogen on any site, affected by the pests, results in massive propagation and dissemination of B. bassiana, the result of which is the epizootic. In addition, a single introduction of the pathogen ensures the preservation and maintenance of the amount at the site for one season and even for several years. A wide range of entomopathogenic activity of B. bassiana and safety in relation to vertebrate animals and plants allows extensive and effective use of biopreparations based on B. bassiana in agriculture. Taking into consideration all facts, mentioned above, the study of issues related to the cultivation of entomopathogenic fungi is of particular relevance. A modified Czapek medium has been obtained, which helps to increase the virulence of conidia of entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin strain B-3 due to the introduction of nutrient yeast broth into the medium. As a result of further modification with the introduction of salts of rare metals: potassium iodide and zinc sulfate, the virulence of conidia has significantly increased, resulting in a shorter time of the death of the test - insects. A simplified nutrient media has been developed for practical application, consisting of sucrose, fodder yeast, sodium nitrate and salts of rare metals that enhances greater virulence of conidia of entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin strain B-3.